Three Conceptions of Intergenerational Relations - Gedvilaitė-Kordušienė, Margarita (Sociologija. Mintis ir veiksmas, 2009)
Due to demographic, economical, social and cultural changes the question of intergenerational relationships is acquiring more attention from family researchers. This article aims to present and asses the critical aspects of contemporary theoretical perspectives, explaining intergenerational relationships. First of all, the relevance of theoretical perspective in the context of social change is presented and the question of intergenerational relationships from historical perspective is shortly analysed. Secondly, three sociological perspectives (solidarity, conflict and ambivalence) which offer different ways to analyse intergenerational relationships are analysed and critical aspects are revealed. Finally, the analysis and critiques of theoretical perspectives allows concluding that in order to see the complete picture of intergenerational relationships the combination of different perspectives or formation of alternative ones are necessary.
Keywords: intergenerational relations; solidarity; conflict; ambivalence